(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
The essay focuses on the principle of self-determination as distinct from the principle of autonomy. The latter, indeed, has to be considered as a premise to self-determination. Both concepts are connected to the essence of the individual, to the idea of human being. The perspective of philosophical reflections is fundamental to the understanding of the respective relationships between these two concepts.